EKSPLORASI KONSEP FISIKA MELALUI AKTIVITAS BERMAIN DAN EKSPERIMEN DI SEKOLAH DASAR - Yani Novita Sari; Efna Yulita; Sinta; Syarifuddin (STKIP Subang, 2025)
Physics learning in elementary schools plays an important role in building scientific understanding, logical thinking, and curiosity from an early age. However, physics concepts are often perceived as abstract and difficult by students when taught through conventional methods. This article aims to examine the exploration of physics concepts through play-based activities and simple experiments in elementary schools. This study uses a literature review method by analyzing textbooks, research articles, and relevant educational references. The results of the study indicate that play-based learning and experimental activities can enhance students’ conceptual understanding, motivation, and scientific process skills. Therefore, integrating play and experimentation in physics learning is essential to create meaningful, enjoyable, and effective learning experiences in elementary education.